Synthesis and Photochemistry of a New Photolabile Protecting Group for Propargylic Alcohols - Ma, Chi; Zhang, Youlai; Zhang, Huan; Li, Junru; Nishiyama, Yasuhiro; Tanimoto, Hiroki; Morimoto, Tsumoru; Kakiuchi, Kiyomi (Synlett, 2017)
A new and efficient thiochromenone S,S-dioxide-based photolabile protecting group for propargylic alcohols is described. Robust protection reactions were developed through copper (II)-catalyzed substitution of propargylic alcohols. Subsequent photodeprotection proceeded smoothly to give the corresponding propargylic alcohols quantitatively within 15 minutes, as demonstrated by 1H NMR spectroscopy and HPLC. Notably, the photoproduct derived from the thiochromenone derivatives showed a high fluorescence quantum yield, permitting monitoring of the reaction progress by fluorescence spectroscopy. A new strategy for the synthesis of triazoles by a one-pot reaction is also presented.
Keywords: thiochromenone dioxides; protecting group; propargylic alcohols; photodeprotection; photolabile groups; triazoles